ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA STAF AKUNTING (STUDI EMPIRIS PADA BEBERAPA PERUSAHAAN SWASTA DI JAKARTA DAN TANGERANG) - DEASY ARIYANTI R (Jurnal Bisnis dan Akuntansi, 2005)
The purpose of this study is to examine the interrelationship between factors, such as organization’s culture, salary’s satisfaction, job satisfaction, motivation and gender that influence work’s productivity. The data are collected through mail survey and contact person from 145 accounting staffs from some of private companies. In Jakarta and Tangerang. Six variables investigated in this study are motivation, job satisfaction, salary’s satisfaction, organization’s culture, gender and work’s productivity. Using Multiple Regression Analysis, the result show that motivation, job satisfaction, salary’s satisfaction, gender directly affect the work’s productivity however organization’s culture do not affect the work’s productivity. Thus, the effort to increase work’s productivity is carried out by increasing motivation, job satisfaction and salary’s satisfaction.